1996
DOI: 10.1063/1.472656
|View full text |Cite
|
Sign up to set email alerts
|

The symmetry breaking problem in the triflouride anion: A multireference approach

Abstract: Articles you may be interested inComment on ''Infrared spectrum and theoretical study of the dinitrogen pentoxide molecule (N2O5) in solid argon'' [A comparison of two approaches to perturbation triple excitation corrections to the coupledcluster singles and doubles method for highspin openshell systemsThe multireference MCSCF and MCSCFϩMP2 methods were applied to the study of the optimum geometry of the F 3 Ϫ anion, its vibrational frequencies and its dissociation energy into F 2 ϩF Ϫ . The system has a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…The T 2 amplitudes for F 3 and F 3 − are 0.14 and 0.16, respectively, which is in agreement with the previously found multireference character of the F 3 − wave function. 34 Dissociation energies of F 2 and F 2 − have been computed according to the equation …”
Section: Calibration Of Computational Approachesmentioning
confidence: 99%
“…The T 2 amplitudes for F 3 and F 3 − are 0.14 and 0.16, respectively, which is in agreement with the previously found multireference character of the F 3 − wave function. 34 Dissociation energies of F 2 and F 2 − have been computed according to the equation …”
Section: Calibration Of Computational Approachesmentioning
confidence: 99%
“…The CAS(7;7,3) model includes the resonance effect. The orbital doubling technique [18,19] can be used to ensure that the size effect is properly treated. For the CAS(7;7,3) wavefunction, the reference configuration of the active space can be written 5a 2 1 1b 2 1 6a 2 1 3b 1 2 2b 0 1 3b 0 1 4b 0 2 7a 0 1 5b 0 2 8a 0 1 : The valence bond structures ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specially tailored multireference wavefunctions have been used to restore the delocalization effect [19,24]. Most recent works have employed the convenient CASSCF method, which provide with sufficient latitude to set the true symmetry wavefunction [18,20,22,27]. Another way to obtain a proper electronic wavefunction is the nonorthogonal orbital CI [21,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mota et al. performed MCSCF and MCSCF+MP2 computations of [F 3 ] − and found that dynamical correlation should be considered for the accurate calculation of the binding energy . In general, however, both the MCSCF+MP2 and single‐reference CCSDT results match well with the experimental data obtained in inert‐gas matrices …”
Section: Introductionmentioning
confidence: 89%